Optimism in English and Arabic Religious Discourse: A Pragmatic Study - Muhammad Abdel Hussein, Nuha; Aliwy Mohammed Al-Husseini, Hashim (Journal of College of Education, 2023)
The present study tries to investigate linguistically optimism in English and Arabic religious discourses. The language of religious discourse is rich to be examined by the researchers. Optimism is carried out by different pragmatic aspects. The study aims at identifying the various pragmatic strategies by which optimism is conveyed through the eclectic model which is adopted to analyse the data. It consists of Searle’s (1969) speech act theory, Grice’s (1975) conversational implicature and Brown and Levinson’s (1987) politeness theory.  The study employs a qualitative content analysis method to analyse three Biblical texts and three Quranic texts that include optimism in the two Holy Books. The   study reveals that optimism is conveyed mainly by the directive, representative speech acts. It is also conveyed by the conversational implicature that is mainly conveyed by words with many connotations. Finally, optimism is mainly carried out by positive politeness strategies such as encouraging, understanding, showing sympathy and promising the reader/listener.
Keywords: Optimism; Pragmatics; Bible